The papillosphincterotomy in hydatid liver cysts opening into the biliary tract. - Perrone, Luis; Estrugo, Roberto; Bounous, ma; Paperán (h), Juan A; Bercianos, Carlos; Lerena, Alberto (Cirugía del Uruguay, 1977)
The authors report on four cases- _of hydatid cyst opening into the hepatic duct in two of them, papillotomy was performed and there was no postoperative bilirrhage; in the remaining two, · papillotomy was not performed and an external biliary fistula appeared. On the basis of this case material the authors emphasize the importance of performing an sphinteroplasty avoiding biliary hypertension. Authors think that the tension is be a consequence of Oddian pathology which is present in varying degree.